Antecedents of intentions to crowdfund luxury brands and projects: Evidence from French consumers. (9th August 2022) - Bryson, Douglas; Atwal, Glyn; Crespi, Roberta
Abstract: Luxury firms, including high‐end watch manufacturers, use crowdfunding as an alternative source of entrepreneurial finance. Respondents indicated that intention to crowdfund luxury brand start‐ups have both external and internal antecedents with the slight majority focusing on the extrinsic factors. The "luxury" proposition exhibits integrated motivation, which is conceptualized and personalized to the tastes of each investor.